New Physics II – Quantum-Dialectical Derivation of New Mass-Energy Relation Invalidates Einstein’s Famous Equation E = mc2 - Malek, Abdul (JOURNAL OF ADVANCES IN PHYSICS, 2024)
The notion that human scale inertial mass and the various forms of tangible energy, like kinetic, heat, light, chemical, gravity, etc., have some kind of equivalence; existed since the time of Isaac Newton. Historically, based purely on epistemological and phenomenological perspective, there has been speculative, theoretical, and experimental attempts based on electrostatic, electrodynamic and relativistic, etc., consideration to deduce a quantitative relation between mass and energy. By the turn of 20th century, a vastly oversimplified and wrongly derived relation ΔE = Δmc2, where E is energy, m inertial mass, and c the velocity of light; has been unjustly attributed to Albert Einstein. This relation presumed to be universally valid for all forms of inertial mass and energy, but without valid evidence, along with the physically and mathematically invalid arbitrary derivation by Einstein; have enjoyed acceptance and is veneration by official science for more than hundred years and still continue. Einstein’s false mass-energy formulation, seems to be due to the unfortunate combination of a number of factor: 1) epistemological misunderstanding; 2) the ill effects of the use of unscientific axiomatic truth of the universal constancy of the (zero-mass) light velocity c, that has given rise to unphysical objects, concepts and notions of reality; 3) workings of (even if unended) mathematical tricks; and 4) most of all, as implied in the mass-energy equation, the wrong conception that the kinetic motion of any object leads to the increase of its inertial mass by the Lorentz gamma factor. All these combined in a negative way to result in the irrational replacement of the velocity v of classical kinetic energy equation with relativistic c. The falsity of the claim of relativistic mass-energy relation would be clear from recent reports that one can derive Einstein’s mass-energy equation from Newtonian mechanics alone, simply by using the wrong concept of relativistic mass increase, instead of a constant inertial mass of classical mechanics. All the concerns about Einstein’s formulation of the mass-energy relation, raise serious doubt about its scientific validity. A more comprehensive ontological approach based on an understanding of the origin of matter and motion in their elementary form, seems to be imperative, to settle the issue of mass-energy relation. Hegel’s philosophy of space and time and his dialectical ontology of the origin of matter and motion, now realized through quantum-dialectics, offers such a paradigm for a scientific and rational derivation of the mass-energy relation.